An evaluation model using the maqasid-al-shariah framework towards liveable city - Norimah Md. Dali (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
This study concentrates on the outstanding research gap that current conventional measurements of liveability lacks religious indicators and sub-indicators. Hence based on this premise this thesis works towards developing an evaluation model for liveability by engaging in the Islamic framework of Maqasid al-Shariah (Objectives of Islamic Laws). Religiosity of human beings is found to be the right prerequisite to set the foundation for liveability planning. The path towards this end has actually been laid by the Creator Himself through the manual called Maqasid al-Shariah. Indeed, worldly pursuits had been governed by greed (prosperity), development and progress negating humanity wellbeing in its holistic sense. Hence, research on the objectives of the Shariah for the individual's liveability and quality of life encompassing the fivefold matter i.e. to safeguard his religion, his life, his intellect, his lineage and his wealth is now indispensable. The rampant environmental disruptions and disasters that gravely affect human liveability and quality of life actually reflect man's failures to perform his role as the "Khalifah" or vicegerent on earth. It should never be attributed as the creator's wrath! This study therefore stresses the role of urban planners and the people living in cities to make cities liveable. To support this goal, this research engaged in data collection involving three semi-structured interviews as its qualitative methodology and one quantitative questionnaire survey of the “guardian” or stakeholders (Urban Planners and Maqasid al-Shariah scholars). Their professional and truthful insights in creating urban liveability and quality for living are vital in developing the liveability measurement model within the Islamic perspective. This thesis designated it as the Islamic Liveability Evaluation Model (ILEM). Rich findings from the Mixed-Method methodology were analysed via ATLAS.ti and Analytic Hierarchy Process (AHP). The former employed the thematic approach while the latter used the Super Decision software to calculate geometric means, weightage, ranking and consistency ratios. The indicators of ILEM are the five Maqasid al-Shariah domains and the sub-indicators by the respective domains are safeguarding religion, widespread religious activities at the neighbourhood and city level, integrated 'aqli and naqli education system, extreme importance in safeguarding the family institution, and wealth generation system that is religious compliant. The choice of Shah Alam as the test case for ILEM serves as an example to evaluate liveability of cities based on the Maqasid al-Shariah framework. Hopefully, the formulation of ILEM by this research is a significant breakthrough to measure liveability of cities for the whole world - both for the Muslim and the Non-Muslim cities alike!